High rates of ammonium recycling in northwestern Lake Taihu and adjacent rivers: An important pathway of nutrient supply in a water column. (September 2019) - Jiang, Xingyu; Zhang, Lu; Gao, Guang; Yao, Xiaolong; Zhao, Zhonghua; Shen, Qiushi
Abstract: The ammonium (NH4 + ) pool in the water column of eutrophic lakes is dynamic and undergoes tightly coupled production and consumption processes because of the metabolism of bacterial and algal communities, particularly in summer. However, NH4 + recycling rates along nutrient gradients at river-lake transitional zones and the extent to which NH4 + regeneration can compensate for consumption have been poorly studied. In August (flood period) and November (normal period), 2016, NH4 + regeneration rates (REGs) and potential uptake rates (Upot s) were measured in northwestern Lake Taihu and adjacent rivers. Results showed that the REGs ranged from 0.09 to 3.30 μmol N L −1 h −1 and the Upot s ranged from 0.20 to 4.88 μmol N L −1 h −1, with higher recycling rates occurring at the river sites. Yet, the lake sites showed significantly higher water column NH4 + demand (WCAD) than that of the adjacent river sites during both seasons ( p < 0.05), probably as a result of the low REGs and the lack of exogenous nitrogen (N) inputs. The flood period showed significantly higher REG and Upot values than those of the normal period ( p < 0.05), probably controlled by higher water temperature and algal biomass. This study confirms that regenerated NH4 + was more important than the ambient NH4 + for sustaining cyanobacterial blooms in northwestern Lake Taihu and indicates that the river–lake transitional zones are key areas for N control in this hypereutrophic system. Graphical abstract: Image 1 Highlights: The higher nutrient load and higher algal biomass lead to higher NH4 + recycling rates that making the rivers the "hotspot" area for the NH4 + recycling. Regenerated NH4 + was the major source compared to the ambient NH4 + to sustaining cyanobacterial blooms in northwestern Lake Taihu. An obvious NH4 + demand in Lake Taihu indicates that N input reduction is likely an effective strategy for controlling algal blooms. Abstract : Regenerated NH4 + is an important and even a dominant source for sustaining cyanobacterial blooms, and an obvious NH4 + demand is found in northwestern Lake Taihu.